2019
DOI: 10.1049/el.2018.7544
|View full text |Cite
|
Sign up to set email alerts
|

Auction‐based power allocation for downlink non‐orthogonal multiple access systems

Abstract: Non-orthogonal multiple access (NOMA) has been considered as one of the key enabling techniques for next-generation wireless networks and the overall performance of these systems largely depends on the power allocation (PA). In this Letter, the authors address the PA problem in a downlink cellular NOMA network. They propose an auction-based mechanism in which the users compete for the transmit power being sold by the base station. Each user places his bid iteratively in order to maximise his own utility. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…The comparison of the proposed PA scheme with the existing algorithms in Wang et al and Lamba et al is shown in Figure for M = 3 and Figure for M = 4. It is quite evident that the proposed PA scheme demonstrates superior performance in terms of the average sum rate of the users for different values of P tot / σ 2 in comparison with the existing algorithms.…”
Section: Simulation Results and Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…The comparison of the proposed PA scheme with the existing algorithms in Wang et al and Lamba et al is shown in Figure for M = 3 and Figure for M = 4. It is quite evident that the proposed PA scheme demonstrates superior performance in terms of the average sum rate of the users for different values of P tot / σ 2 in comparison with the existing algorithms.…”
Section: Simulation Results and Discussionmentioning
confidence: 87%
“…Furthermore, we prove the convergence of the game to a unique Nash equilibrium (NE) theoretically. The proposed auction game yields better results in terms of the average sum rate of users as compared with the existing algorithms in Wang and Lamba et al…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…The authors of Reference [12], introduced an auction-based resource allocation for software-defined networks. The auction-based power allocation game between users in NOMA network was addressed by Lamba et al [13]. The base station (BS) played the auctioneer while users are the bidders.…”
Section: Introductionmentioning
confidence: 99%